RATIONALIZING THE USE OF CHEMICAL FERTILIZERS BY USING SOME MICRO-ORGANISMS AND THEIR IMPACT ON THE PRODUCTIVITY AND QUALITY OF OENOTHERA BIENNIS L. PLANT - Maie Mohsen; Naglaa Elbohy; Nahed El Shayeb (Scientific Journal of Flowers and Ornamental Plants)
In order to examine the effects of bio-agent technology, the current study, which used a complete randomized block design, was conducted in the Farm of Cairo University's Pharmacy Department throughout the two succeeding growing seasons of 2020/2021 and 2021/2022. In order to investigate the growth, herb yield, fixed oil %, and fixed oil yield and its components, manipulation of a few plant-growth-promoting PGPs such as Azotobacter chroococcum, Azospirillum lipoferum, and Bacillus polymyxa under 50, 75, and 100% of N fertilizer on Oenothera biennis L. (evening primrose) was tested. Before planting, seeds were soaked for half an hour in a distillated water. Plants were sprayed with the bioagent suspension four times a month after planting during the two seasons in which these bioagents. The plant height, number of branches/plant, number of pods/plant, herb fresh and dry weights per plant (g), seed weight/plant (g), fixed oil % in seeds, and fixed oil production per plant (ml) were significantly increased after inoculation with these bio-agents. The soil's nitrogenase and dehydrogenase activity, total carbohydrates (%), and percentages of N, P, and K were all measured chemically. When plants were treated with Azotobacter chroococcum (Ac), Azospirillum lipoferum (Al) and Bacillus polymyxa (B) in the presence of 75% N fertilizer, the maximum rise in these parameters were recorded. The plants that received 50% of their N fertilization had the lowest mean of all the parameters in both seasons. The same process yielded the highest percentages of linoleic, oleic, palmitic, and linolenic acids in the fixed oil. Additionally, the plants receiving this treatment showed the highest percentages of total carbohydrates, N, P, and K in the soil as well as the highest levels of nitrogenase and dehydrogenase activities.